2019
DOI: 10.1007/s11104-019-04366-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean woody plant specialized metabolites affect germination of Linum perenne at its dry and upper thermal limits

Abstract: Aims: Soil temperature and moisture impact plants not only during growth and survival but also 9 during seed germination and interaction of seeds with the chemical environment. The quantitative 10 impacts of either temperature and moisture or plant specialized metabolites (PSM) on germination 11 are widely studied. However, the combined effect of PSM and moisture or temperature on 12 germination remains poorly understood. 13 Methods: We addressed this issue by studying the effect of PSM extracted from four Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Although these tests show specificity of NOR for different species, it must be taken into account that the phytotoxicity of a natural compound can be affected by environmental conditions (light, temperature, etc.) [ 31 , 32 , 33 ]. This point must be considered when analyzing the results.…”
Section: Discussionmentioning
confidence: 99%
“…Although these tests show specificity of NOR for different species, it must be taken into account that the phytotoxicity of a natural compound can be affected by environmental conditions (light, temperature, etc.) [ 31 , 32 , 33 ]. This point must be considered when analyzing the results.…”
Section: Discussionmentioning
confidence: 99%
“…Drought applied during the first year, or on more sensitive target species, may lead to different results. For instance, Hashoum et al (2019) showed that drought and allelopathy from Cotinus interact to decrease the germination of the herbaceous Linum perenne L. In addition, under natural conditions drought can be more pronounced that the drought treatment applied here and reach lethal levels for seedlings, particularly under the expected climate change (Giorgi and Lionello 2008). In that case, an inhibition of oak seedling root development by neighboring allelopathic species such as Cotinus and Pinus could reduce survival probability in case of more pronounced water stress.…”
Section: Drought Affect Q Pubescens Seedlings Physiology and Growth But Do Not Interact With Allelopathymentioning
confidence: 94%